Utility of low-profile visualized intraluminal support (LVIS™) stent for treatment of acutely ruptured bifurcation aneurysms: A single-center study - Liu, Changya; Guo, Kaikai; Wu, Xinxin; Wu, Linguangjin; Cai, Yike; Hu, Xuebin; Fang, BangJiang (Frontiers in Neurology, 2023)
Objective: Stent-assisted coiling has been increasingly used in the treatment of intracranial aneurysms. However, its application in ruptured bifurcation aneurysms remains controversial and challenge. This study aimed to present the safety and feasibility of low-profile visualized intraluminal support (LVIS™, LVIS and LVIS Jr.) stent for acutely ruptured bifurcation aneurysms. Methods: A total of 186 patients with acutely ruptured intracranial aneurysms arising at the bifurcation were admitted to our hospital between January 2017 and December 2021. The clinical data and angiographic results of patients treated with LVIS™ stent-assisted coiling were analyzed. Results: Forty-one patients with 41 acutely ruptured intracranial aneurysms at the bifurcation were collected, which comprised 22% (41/186) of all admitted patients. All stents were successfully implanted. According to the immediate angiographic results, 29 aneurysms (70.7%) were achieved completely occlusion. Intraoperative thrombosis and hemorrhage occurred in two and one cases, respectively. No postoperative thrombosis or rebleeding event was observed. The clinical follow-up of all patients revealed that 38 (92.7%) of cases had favorable outcomes (modiﬁed Rankin scale: 0-2). The angiographic results were avaliable for the 36 patients during the follow-up period, revealed complete occlusion was achieved in 30 patients (83.3%) and residual neck in six patients. Conclusion: The LVIS™ stent-assistant coiling is a safe and feasible option for acutely ruptured bifurcation aneurysms. Further studies with a prospective design, larger sample size and long-term follow-up are needed to validate these findings.